Implementasi Profesionalisme Guru dalam Menciptakan Lingkungan Belajar yang Responsif pada Pendidikan Anak Usia Dini - Hasbi Hasbi (FKIP UNSULTRA, 2026)
Early Childhood Education (ECE) plays an essential role in providing comprehensive developmental stimulation for children through a high-quality learning environment. One of the main factors determining the success of ECE services is teacher professionalism as educators who directly interact with children. This study aims to analyze the implementation of teacher professionalism in creating responsive learning environments in early childhood education through a literature review. This research employed a library research method with a descriptive qualitative approach. The data were obtained through an analysis of various literature sources, including scientific journal articles and relevant reference books related to ECE teacher professionalism, educator competencies, and responsive learning environments. Data analysis was conducted using content analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that ECE teacher professionalism contributes significantly to the creation of responsive learning environments through five main aspects: strengthening pedagogical competence, developing social-emotional interactions, creating safe and inclusive learning environments, implementing innovative learning strategies, and engaging in continuous professional development. Professional teachers are able to understand children’s characteristics and individual needs, enabling them to design meaningful learning experiences that are appropriate to children’s developmental stages. Therefore, improving teacher professionalism in early childhood education is an important strategy for achieving child-centered, meaningful, and developmentally appropriate learning practices that support children’s optimal growth and development.